2019
DOI: 10.12957/demetra.2019.43189
|View full text |Cite
|
Sign up to set email alerts
|

Duração Do Aleitamento Materno E Sua Associação Com Características Maternas E Orientações Sobre Incentivo À Amamentação Recebidas No Pré-Natal Em Unidades Básicas De Saúde Da Família De Um Município Do Nordeste Brasileiro

Abstract: Objetivo: Estimar o tempo de aleitamento materno entre crianças atendidas na rede pública de saúde e verificar diferenças segundo características maternas e da atenção pré-natal (número de consultas e orientações profissionais). Métodos: Pesquisa transversal realizada em 16 unidades básicas de Saúde da Família com 204 crianças nascidas em 2009, em um município do Nordeste brasileiro. A coleta de dados ocorreu de forma retrospectiva em 2011, por aplicação de questionário às mães das crianças. Utilizou-se a anál… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
1
0
8

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 25 publications
3
1
0
8
Order By: Relevance
“…Many studies reported a significant and positive association between counselling and EBF. In the present study, mothers who had more than 8 prenatal medical appointments were more likely (OR = 1.88) to breastfeed more, which is in agreement with the results of other studies [ 29 , 35 , 36 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Many studies reported a significant and positive association between counselling and EBF. In the present study, mothers who had more than 8 prenatal medical appointments were more likely (OR = 1.88) to breastfeed more, which is in agreement with the results of other studies [ 29 , 35 , 36 ].…”
Section: Discussionsupporting
confidence: 93%
“…It was noted that mothers with more than two children were more susceptible (OR = 1.88) to breastfeeding than mothers with up to two children, confirming results from other studies [34,36].…”
Section: Discussionsupporting
confidence: 87%
“…Mothers who attended more than 8 prenatal visits were more likely (OR = 1.88) to breastfeed than mothers who attended fewer than 8 visits. The results of the present study are in agreement with those of (39), which states that the attendance of 6 or more prenatal visits may contribute to an increase in the duration of breastfeeding.…”
Section: Factors That Interfere With Breastfeedingsupporting
confidence: 92%
“…The location of residence was not related to breastfeeding. This contrasts with (39), in which the duration of breastfeeding was higher among children living in rural areas.…”
Section: Factors That Interfere With Breastfeedingmentioning
confidence: 61%
“…Desempenhando papel relevante na rede de apoio à gestante e à nutriz, o pilar da Atenção Primária em Saúde (APS) também é indispensável para a promoção, proteção e apoio ao AM. Deste modo, foram implantadas diversas ações de incentivo à prática, tendo como exemplos a "Iniciativa Unidade Básica Amiga da Amamentação", que objetivou fomentar os "10 passos" no âmbito da AB por meio da capacitação profissional 21,17 ; e a "Rede Amamenta Brasil", a qual provocou uma reformulação e a pactuação das ações no fluxo de atendimento interdisciplinar ao binômio mãe-filho 3,17 .…”
Section: Métodounclassified